2018
DOI: 10.1093/infdis/jiy443
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Attack Rates of Seasonal Influenza Infection: Results of the Southern Hemisphere Influenza and Vaccine Effectiveness Research and Surveillance (SHIVERS) Seroepidemiologic Cohort Study

Abstract: Measurement of anti-neuraminidase antibodies in addition to anti- hemagglutinin antibodies may be important in capturing the true influenza infection rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
41
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 35 publications
13
41
2
2
Order By: Relevance
“…All of these studies identified the exposure of healthcare personnel to household contacts as having the highest odds of respiratory illness after exposure, with ORs ranging from 2.9 to 16.7. These data are also supported by several studies documenting that the number of children in a household is a risk for influenza in adults, which is to be expected since the seasonal attack rate for influenza in children is higher than that for adults [13,16,25].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…All of these studies identified the exposure of healthcare personnel to household contacts as having the highest odds of respiratory illness after exposure, with ORs ranging from 2.9 to 16.7. These data are also supported by several studies documenting that the number of children in a household is a risk for influenza in adults, which is to be expected since the seasonal attack rate for influenza in children is higher than that for adults [13,16,25].…”
Section: Discussionsupporting
confidence: 74%
“…The variable whose elimination caused the least significant deterioration of model fit was removed and the process repeated until all variables were significant at P 0.20 [24]. Age and sex were retained as they are associated with incidence of influenza and other viral respiratory infections [25]. Collinearity of eligible variables was investigated, and the final multivariable model was assessed for fit, influential observations and overfitting.…”
Section: Discussionmentioning
confidence: 99%
“…to the HI assay that only measures antibodies that prevent virus attachment to red blood cells. While the LIPS HA seropositive controls may represent true subclinical infections, 10,11 cross-reactivity of anti-H1 antibody to previous non-H1N1pdm09 infections is possible. 8 The main strength of this study was access to human samples from a well-characterized cohort, combining national registry data, self-reported questionnaire data and HI titre data.…”
Section: Discussionmentioning
confidence: 99%
“…For mild cases, a clinical diagnosis based on symptoms may suffice, 9 or medical care may not be sought; moreover, a large proportion of infected individuals remain asymptomatic. 10,11 Consequently, most cases of influenza infection remain undetected, 6,7 underscoring the need for other sources of information, such as questionnaires, health registries and biological specimens, for ascertaining or estimating the infection status of an individual. In prospective studies, direct laboratory testing requires active screening of participants, which is labour intensive and expensive, and typically limited to clinical vaccine trials.…”
Section: Introductionmentioning
confidence: 99%
“…However, NA evolves at nearly the same rate as HA and has similar signatures of adaptive evolution [12]. Additionally, recent work showed the importance of anti-NA antibodies to protective immunity through natural infection and vaccination [13,14]. This suggests that NA evolution is a substantial contributor to the changing antigenic properties and dynamics of influenza viruses.…”
mentioning
confidence: 99%